Near-UV light assisted green reduction of graphene oxide films through l-ascorbic acid. Issue 1 (2nd January 2021) - Regis, Jaime; Vargas, Sebastian; Irigoyen, Andrea; Bramasco-Rivera, Elsa; Bañuelos, Jose L.; Delfin, Luis C.; Renteria, Anabel; Martinez, Ulises; Rockward, Tommy; Lin, Yirong
ABSTRACT: Recent studies have highlighted the effects of various stimuli on the chemical reduction of graphene oxide (GO) through green reductant L-ascorbic acid (L-AA); however, the combination of near ultraviolet (NUV) light to increase the reduction rate has yet to be thoroughly explored. In this study, drop-casted GO films were subjected to chemical reduction through L-AA with various levels of exposure under 405 nm NUV radiation. The structure and uniformity of GO stackings that form the film were characterized through scanning electron microscopy (SEM) and wide-angle x-ray scattering (WAXS). Additionally, WAXS was used to track the removal of oxygen-containing functional groups along with Fourier-transform infrared (FT-IR) spectroscopy and x-ray photoelectron spectroscopy (XPS) as a function of L-AA and NUV light exposure times. XPS results demonstrated that the interaction between L-AA and NUV exposure has a significant effect on the reduction of films. Furthermore, the results that yielded the highest reduction (C-C bond concentration of 60.7%) were the longest L-AA and NUV light exposure times (48 hours and 3 hours, respectively). This report provides a study on the effects of NUV on the green reduction of GO films through L-AA with potential application in solar energy and chemical sensing applications. Graphical abstract: uf0001